Comparability of Fidelity Measures for Assessing Tier 1 School-Wide Positive Behavioral Interventions and Supports. (October 2017) - Mercer, Sterett H.; McIntosh, Kent; Hoselton, Robert
Several reliable and valid fidelity surveys are commonly used to assess Tier 1 implementation in School-Wide Positive Behavioral Interventions and Supports (SWPBIS); however, differences across surveys complicate consequential decisions regarding school implementation status when multiple measures are compared. To address this concern, the current study (a) provides updated convergent validity estimates for five fidelity measures, (b) tests mean differences in scores and reports the percentages of schools meeting recommended implementation criteria by measure, and (c) investigates sensitivity of the measures to differences between schools at varied levels of implementation. Across most surveys, convergent validity estimates were moderate ( r = .59–.71), and mean differences were negligible for all surveys other than the School-Wide Evaluation Tool (SET), on which higher scores were more likely to be obtained. Despite higher average scores, the SET classified similar percentages of schools as adequately implementing compared with other measures with a 70% implementation criterion, but fewer schools when compared with measures with an 80% criterion. Compared with other measures, the PBIS Self-Assessment Survey (SAS) was more sensitive to differences among schools at higher levels of implementation. Implications for SWPBIS research and fidelity assessment are discussed.